2019
DOI: 10.1002/jgc4.1098
|View full text |Cite
|
Sign up to set email alerts
|

Secondary findings: How did we get here, and where are we going?

Abstract: The American College of Medical Genetics and Genomics (ACMG) recommendations for reporting of incidental (now “secondary”) findings in clinical exome and genome sequencing (Green et al., Genet Med 15:565, 2013) is an often cited and sometimes misapplied professional guideline. To best approach the current state of secondary findings (SFs) in genomic medicine, and consider their impact, it is helpful to understand how and why the guideline was created. Of particular importance is the context ‐ the state of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…A conflict of interest might arise between the researcher's or clinician's ''duty to inform'' at-risk patients and family members and the individual's ''right not to know''. 58 Furthermore, genetic testing could infringe on family privacy because results indirectly provide information about family members 59 and may include mispaternity. These possibilities should be discussed with the patient before testing.…”
Section: Key Pointsmentioning
confidence: 99%
“…A conflict of interest might arise between the researcher's or clinician's ''duty to inform'' at-risk patients and family members and the individual's ''right not to know''. 58 Furthermore, genetic testing could infringe on family privacy because results indirectly provide information about family members 59 and may include mispaternity. These possibilities should be discussed with the patient before testing.…”
Section: Key Pointsmentioning
confidence: 99%
“…Yet communicating such results requires special attention to both the personal and medical relevance for patients. The development of clinical genetics has added another dimension to the issue of secondary findings, prompting a global debate as to whether clinically relevant genetic mutations should be communicated to patients, and under which circumstances (Ormond et al, 2019). Definitions of the terms used are provided in Table 1.…”
Section: Term (Research Context) Definitionmentioning
confidence: 99%
“…We have discussed the difficulties with these ACMG guidelines (19). Studies have shown low yield from these guidelines (65, 66).…”
Section: Caveatsmentioning
confidence: 99%